The Challenge of Potential Drug–Drug Interactions Among People Living With HIV on Antiretroviral Therapy: A Cross-Sectional Study in Selected Provinces in China - Xia, Huan; Gao, Liying; Gong, Xiaowen; Zaongo, Silvere D.; Zhang, Tong; Wu, Hao; Ma, Ping; Huang, Xiaojie (Frontiers in Pharmacology, 2020)
Abstract Objectives: Potential Drug-Drug Interactions (DDIs) are a significant therapeutic threat among human immunodeficiency virus (HIV)-positive individuals on antiretroviral (ARV) medications. DDIs involving ARV drugs in mainland China are unknown and insufficiently described. Herein, we investigated the prevalence and frequencies of potential ARV DDIs in Chinese people living with HIV(PLWH), then we assessed the risk factors associated with potential DDIs. Methods: This study was conducted with HIV-positive adults undergoing ARV medications from multiple centers across China. The latest prescription of each participant was evaluated for potential DDIs using the Liverpool HIV drug interaction database. Multivariable logistic regressions were used to evaluate the factors associated with DDIs. Results: Among 600 PLWH recruited, at least one non-HIV co-medication was observed in 511 (85.2%) individuals. A total of 2566 DDIs were identified, of which 11 (0.43%) and 311 (12.89%) were of contraindicated (red-flags) and dosage/timing adjustment required (orange-flags), respectively. Multivariate regression analysis revealed a higher risk of clinically significant DDIs (red- and orange-flagged comedication) associated with: the use of boosted protease inhibitors (p < 0.0001), boosted integrase strand transfer inhibitors (p < 0.0001), and non-nucleoside reverse transcriptase inhibitors-based ARV regimen (p < 0.0001); or the use of antiinfectives for systemic use (p < 0.0001), cardiovascular system drugs (p < 0.0001), nervous system drugs (p < 0.0001), fungal infection (p = 0.0071), and Herpes simplex virus infection (p = 0.0231). Conclusions: Potential DDIs and inappropriate medications constitute a burden for people living with HIV in China. The knowledge of DDIs patterns and the scan for DDIs is crucial. Indeed, they can help to prevent drug-related adverse outcomes in such immunodeficient population.